Knowledge-based human resource management, logistics capability, and organizational performance in small finnish logistics service providers - Pietro Evangelista; Aino Kianto; Henri Hussinki; Mika Vanhala; Anna-Maija Nisula (Logistics, 2023)
Background: In the current knowledge age, the performance of logistics firms increasingly depends on knowledge and capabilities they can leverage in value-creation processes. The objective of this paper is to investigate the relationship between knowledge-based human resource management (HRM) practices and organizational performance mediated by logistics capability. Methods: Data from 93 small Finnish logistics service providers was collected by a questionnaire survey. Structural equation modeling and partial least squares analysis were used to test the hypothesized relationships between HRM practices and the organizational performance of logistics companies, as well as the mediating impact of logistics capability. Results: The results demonstrate that logistics capability fully mediates the relationship between HRM practices and the organizational performance of small logistics companies. Each of the three knowledge-based HRM practices-knowledge-based recruitment, training and development, and motivation-significantly influences logistics capability, which is, in turn, associated with the organizational performance of companies. Conclusions: This paper is one of the few among discussing knowledge-based HRM practices in logistics service research. The paper contributes to the literature on logistics by demonstrating the value of knowledge-based HRM practices in acquiring, developing, and leveraging knowledge to create organizational capabilities and ensure organizational performance. This study provides an improved understanding of the role of HRM and the resulting logistics capability in the performance of small logistics service companies.
Keywords: 650; Finland; HRM practices; knowledge management; logistics capabilities; performance; questionnaire survey; small logistics service companies